(untitled) (Scottish Historical and Archaeological Internet Reports, 2012)
A total of 57 dates were obtained from charcoal and human bone. Three Mesolithic dates came from the large pit. The remainder were from the cremation burials. With the exception of two slightly earlier dates which may have come from old charcoal they were all early Bronze Age.